Self-scanning and self-control: A field experiment on real-time feedback and shopping behavior - Natalia Montinari; Emma Runnemark; Erik Wengström (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
Payment and checkout at retail stores is increasingly being replaced by automated systems. One recent technological invention in this area is mobile self-scanning in which customers carry a mobile scanner while shopping. Mobile self-scanners give real-time feedback on spending. The device increases price saliency and enables customers to keep track of the total amount spent. Using a field experiment, we test if mobile self-scanning affects shopping behavior. Consumers of two grocery stores were allocated randomly to use a mobile self-scanner or not. Overall, we find that using the self-scanner has a negative but insignificant effect on total amount spent. However, the response to using the scanner is heterogeneous and for customers with low self-control, it significantly reduces both their spending and number of items bought when using the mobile scanner. Moreover, we find that consumers with low self-control are more likely to use the self-scanner than individuals with high self-control. Taken together, our results suggest that sophisticated individuals, that is, individuals who are aware of their self-control problem, use the scanner to control their spending.
Keywords: D01; D12; M30; 330; Self-scanning; Self-control; Shopping Behavior; Real-time Feedback; Field Experiment